Respostas
respondido por:
14
Ola Mendes
vamos encontrar o terceiro lado pela lei dos cossenos
x² = 2² + (1 + √3)² - 2*2*(1 + √3)*cos(60)
x² = 4 + 1 + 2√3 + 3 - 2 - 2√3
x² = 4 + 1 + 3 - 2 = 6
x = √6
perímetro
P = 2 + 1 + √3 + √6
P = 3 + √3*(1 + √2) (B)
.
vamos encontrar o terceiro lado pela lei dos cossenos
x² = 2² + (1 + √3)² - 2*2*(1 + √3)*cos(60)
x² = 4 + 1 + 2√3 + 3 - 2 - 2√3
x² = 4 + 1 + 3 - 2 = 6
x = √6
perímetro
P = 2 + 1 + √3 + √6
P = 3 + √3*(1 + √2) (B)
.
mendesnanan:
esses * significa o que ?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás